THE INFLUENCE OF MARKETING MIX AND SERVICE QUALITY ON HOME PURCHASING DECISIONS THROUGH CORPORATE IMAGE - Aetken Ibrahim; Suparman Parintak; Muhammad Aqsa; A. Nadirah; Muh. Yusuf Q (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to analyze the effect of marketing mix and service quality on purchasing decisions with corporate image as a mediating variable, a case study on housing consumers of PT. Aneka Wijaya Putra in Malili, East Luwu Regency. Marketing mix and service quality are key factors believed to be able to influence consumer purchasing decisions, while corporate image is identified as an important element that can strengthen or weaken the influence of both factors. This study uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to housing consumers of PT. Aneka Wijaya Putra with the determination of the number of samples using the MoE formula so that 96 samples are obtained. The data obtained are analyzed using interferential analysis techniques to test the direct and indirect effects between the research variables. The results show that marketing mix and service quality directly affect corporate image and purchasing decisions. Corporate image does not have a significant effect on purchasing decisions. Marketing mix has a positive but not significant effect on purchasing decisions through corporate image. Conversely, service quality shows a positive and significant effect on purchasing decisions through corporate image. These findings indicate that although marketing mix strategies are important, superior service quality is more dominant in forming a positive corporate image, which ultimately drives consumer purchasing decisions.